EL TABERNÁCULO PARA EL RETABLO DE LA CAPILLA DEL SAGRARIO O DE LOS AYALA EN LA CATEDRAL DE SEGOVIA - Prados, José María (Imafronte, 1989)
The well-known reredos carved by Churriguera for the Chapel of the Sacrarium (also called The Ayala’s Chapel) in the Carhedral of Segovia, made from 1686 on, was completed several years later with the magnificent tabernacle of the Tomé, the execution of which was carried out offer its contracting by Antonio Tomé en 1718. It is just the study of this tabernacle the subject of this paper. We analyse the details of its history and execution upon the basis of important documents from the Cathedral Archives; we also put attention to other works in the Chapel. We include a valuation of the mentioned tabernacle or «ostensorio»; ir does not reach the importante of other works of this family, such as the «Transparente» of Toledo, but it represents a new trend in the art of the Tomé, leading to the mature style.